Do Sleepy Plants Sleep at Night? (2011)
Sleepy plants are perhaps the most fun part of the legume family. Quite similar to their sisters in appearance, they have the peculiarity of closing their leaves in response to certain stimuli such as friction or loud noise. Hence its scientific name: Mimosa pudica, and its many common names: shameful, moriviví, poppy, and sleepyhead, to name just a few. Read further to know more about this plant